(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Nateglinide is practically insoluble in water, sparingly soluble in strong acid; soluble in strong bases. It is an anti-diabetic, effective in treatment of diabetes. Solubility of Nateglinide is increased by using 0.1M Piperazine as a hydrotropic agent. Nateglinide showed the maximum absorbance at 220nm. At this wave length, hydrotropic agent and other tablet excipients did not show any significant interference in the spectrophotometric assay. The developed methods were found to be linear in the range of 5-30µg/ml with correlation coefficient r2 of 0.9966. The mean percent label claim of tablets of Nateglinide in formulation estimated by the proposed method was found to be 98.05%, 98.07%, 99.15%. The developed methods were validated according to ICH guidelines and values of accuracy, precision and other statistical parameters were found to be in good accordance with the prescribed values. As hydrotropic agent was used in the proposed methods, these methods were eco-friendly and it can be used in routine quantitative analysis of drug in bulk and dosage form in industries.